SIKAP YANG BERHUBUNGAN DENGAN UPAYA PENCEGAHAN PENULARAN TB PARU KONTAK SERUMAH DI WILAYAH KERJA PUSKESMAS PABENTENGAN KABUPATEN GOWA - Karno, Yosef Marsianus; Pattimura, Nastain Abubakar (STIKES Pasapua Ambon, 2022)
Introduction: World Health Organization (WHO) views Tuberculosis (TB) as one of the oldest known infectious diseases and still becomes the leading cause of death. Indonesia contributes as much as 45% of the world total cases of TB. The prevalence of TB in South Sulawesi is 0.36%. Pabbentengan Community Health Centre is one of the health centers with the highest TB case in Gowa. In 2019, 47 cases of TB were recorded and among of the cases 3 were household contacts. The increasing of TB case is caused by socio cultural factors such as knowledge, family, job dan income. This research aimed to: Find out the relation between behavour and the efforts to prevent the transmission of TB in household contact. Method: This research was a quantitative, analytic study with a Cross Sectional approach. The population of this research was TB patients and family members of TB patients with a total sample of 99 respondents. Data collection method used in this research was questionnaire. When collecting data was done, the next steps were editing, coding, entry, cleaning, and tabulating data. The data were then processed with a computer on the IBM SPSS Statistics 21 program. Results: The result of this research showed p-value Behavior of 0.022. Conclution: there are relations between knowledge, behavior, family support and income with the effort to prevent the transmission of TB patients in household contact. As for job, there is no significant relation